Planning and control using Microsoft Project 365 and 2021. (Packt Publishing, 2023)
This course equips participants with the essential skills to effectively plan, schedule, and control projects, covering resource-constrained and un-resourced project management; the course explores the features of Microsoft Project 365 and its 2021 version. You will create projects, allocate resources, track progress, analyze critical paths, generate reports, and gain proficiency in project planning and control to enhance project success. The course covers project planning and control using Microsoft Project (versions 365, 2021, 2019, 2016, 2013). It includes creating projects, scheduling without resources, updating schedules, managing roles and resources, controlling projects with resources and costs, and utilizing various tools and utilities. You will learn to manage projects, demonstrate delays and accelerations, and apply filters, layouts, and baselines. Upon completion, you will have acquired intermediate-level skills in planning and controlling projects using Microsoft Project and creating and managing projects, scheduling tasks with/without resources, assigning roles and resources, and controlling project progress with costs and resources. You will have learned to utilize filters, layouts, and baselines, update project schedules with completed/incomplete work, and demonstrate schedule delay and acceleration. What You Will Learn Master project planning and develop a Work Breakdown Structure (WBS) Schedule efficiently with task dependencies and critical path analysis Manage resources, track progress, control costs, create custom reports Use baselines, filters, and layouts to manage project efficiency Gain insight into project expenses and analyze financial budget variances Explore techniques to schedule projects with and without resources Audience This course aims to deliver content to project managers and schedulers wishing to use the software to schedule and control projects. Program managers, project managers, and project control staff evaluate the software against their organizational requirements. This course also helps individuals to plan and control projects with/without resources up to an intermediate level using Microsoft Project. The prerequisites for the course include a background in project management processes, proficiency in planning and controlling projects, and basic computer skills. About The Author Paul E. Harris: Paul Harris holds an honors degree in civil engineering from the UK and is a Certified Cost Engineer through AACEI International, a PRINCE2 Registered Practitioner, and a "Managing Successful Programmes" Registered Practitioner. He has several years of experience in project control and has assisted many companies with project control systems. His Australian company, Eastwood Harris Pty Ltd., offers consulting and training worldwide on Microsoft Project/Primavera software. He has published user guides/training manuals for Primavera SureTrak, P3, and Microsoft Project users. He focused on developing books on project management methodologies, such as PRINCE2 and the PMBOK℗ʼ Guide on using Primavera P6 to plan and control projects.